Genome Divergence and Dynamics in the Thin-Tailed Desert Sheep From Sudan - Abied, Adam; Ahbara, Abulgasim M.; Berihulay, Haile; Xu, Lingyang; Islam, Rabiul; El-Hag, Faisal M.; Rekik, Mourad; Haile, Aynalem; Han, Jian-Lin; Ma, Yuehui; Zhao, Qianjun; Mwacharo, Joram M. (Frontiers in Genetics, 2021)
With climate change bound to affect food and feed production, emphasis will shift to resilient and adapted indigenous livestock for long-term sustainability of livestock agri-food systems. However, indigenous livestock comprise several varieties, strains and ecotypes whose genomes remain poorly characterized. We investigated genome variation in an African thin-tailed Desert Sheep sampled in Sudan, using 600K genotype data generated from 121 individuals representing five ecotypes. We included data from 18 fat-tailed and 46 thin-tailed sheep from China to investigate shared ancestry and for comparative genomic assessment. We observed a clear genetic differentiation between the African thin-tailed Desert sheep and the Chinese thin-tailed and fat-tailed sheep suggesting a broad genetic structure between the fat-tailed and thin-tailed sheep in general, and at least two autosomal gene pools comprise the genome profile of thin-tailed sheep. Further analysis detected two distinct genetic clusters in the African thin-tailed Desert Sheep and the Chinese thin-tailed sheep, respectively suggesting fine-scale and a complex genome architecture in the thin-tailed sheep. Selection signature analysis suggest differences in adaptation, production, reproduction and morphology underlie the fine-scale genetic structure in the African thin-tailed Desert Sheep. This may need to be taken into account in the design of breeding programs and genome-wide association studies.